Peran Ganda Perempuan : Reproduksi dan Produksi - Marzuki, Sitti Nikmah (PSW, 2011)
The existence of repression against women making women were not considered equal to men. By limitation out and work can mean that women were not given the same opportunity to develop skills as men. How women in the absence of freedom for a career ranged only in three places: mattresses, kitchens, and wells. This means that women are not given the opportunity to learn and develop their intellectual abilities through work practices. The things done is about to wash clothes, bathe at the same time raising children, cooking and serving her husband. So this is where the practice of discrimination against womens time is eliminated.Discrimination experienced then demanded women should perform his role in two aspects, in addition working at home to take care of the family also had to work outside the home to support the husbands income to be more prosperous. Working at house is not considered a profession because it does not make money. So women should have the dual role of reproductive and productive. Housework is not considered as work for economic reasonsÂ and consequently the culprit is not rated to work. This needs to be clarified that the position of women in his work as housewives, whereas housewives workload is much longer than women who work outside the home.